Presenting the model of early academic ability of preschool children based on parenting styles with the mediating role of emotional intelligence - Moghbel Baerz, Farzaneh; Ghorban Jahromi, Reza; Dortaj Raberi, Fariborz (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2022)
Background and Aim: The aim of this study was to present a model of early academic ability of preschool children based on parenting styles with a mediating role of emotional intelligence. Method: The research method was descriptive and in terms of statistical analysis, and correlation, based on path analysis. The statistical population of this study consisted of all mothers and preschool children of boys and girls in Tehran in 1400-99, from which 350 people (175 girls and 175 boys) were selected by multi-stage cluster sampling. In this study, the tools of early academic ability (Wright and et al., 1997), parenting styles (Bamrind, 1997) and emotional intelligence (Bradbury and Graves, 2005) were used, all of which had acceptable validity. Spss-V23 and LISREL-8.8 software were used to analyze the data. Results: The results of the path analysis showed that the research model has a good fit. The findings indicated that all three parenting methods of parents have a direct and significant effect on emotional intelligence and also on the early academic ability of preschool children. Also, the direct and significant effect of emotional intelligence on the early academic ability of preschool children is confirmed. Conclusion: These results alert the need for more attention of education stakeholders, schools and consequently parents, to the category of efficient parenting style and emotional intelligence appropriate to the educational period of children to improve their academic ability.